칠정상(七情傷)으로 인한 두통 환자의 심박변이도(Heart Rate Variabillity)에 관한 고찰 - 박선영; Sun Yong Park; 최철홍; Cheol Hong Choi; 정대규; Dae Kyoo Chung; 고경모; Kyung Mo Ko (동의신경정신과학회지, 2008)
Objects : To treat psychogenic headache patients, doctors have to amplify on the headache caused by emotional stress to patients, and assist the patients to cope with difficulties. So, we invesgated HRV of the headache patients caused by Chiljungsang and would like to apply to the clinical treatment. Method : Our study measured time and frequency domain HRV indicies(5-min resting study) of 123 headache patients caused by emotional stress. Standardized tests of HRV allow a quantitative esmation of autonomic nervous system function. Results & Conclusions : 1. The study classed as aspects of the head pain showed the differences in RMS-SD(square root of mean squared difference of successive NN intervals) band, HF(high frequency) band significantly. 2. The male headache patients showed higher all the indicies except heart rate compared to the female patients, significantly in SDNN(standard deviation of NN interval), TP(total Power), HF band. 3. As the patients grow older, SDNN, RMS-SD band was lower and LF(low frequency) band, LF/HF ratio higher significantly. The beginning age lower, SDNN, RMS-SD band was higher significantly. The duration of the disease longer, LF band, LF/ HF ratio was higher significantly.